Learning Model of Fundamental Long Jump Movement Based On Game Approach - Sumantri, Mohamad Syarif (Universitas Negeri Semarang, 2015)
This study aims to develop and implement a process of learning the basic movement in long jump through a small game approach for primary education second grade students, The ultimate goal of this research is the development of a learning model produces basic movement in long jump through a small game approach, which is expected to help the process learning that there are at the practice be more effective, efficient and increase the attractiveness for students in the learning process of physical activity following the basic movement, especially the long jump. This research practically assist as an input for the relevant institutions in developing and teaching physical education in elementary schools so that the quality of teaching physical education to be more optimal. The study methodology is designed to research and development approach (Research and Development) with Borg and Gall models and data analysis techniques used are the percentage of quantitative descriptive analysis. This technique is used to analyze the quantitative data obtained from the questionnaire evaluation of teaching physical education experts regarding the results of the products developed. Subject retrieval techniques applied in this study is purposive sampling, which is also known as sampling considerations or based on certain considerations. The results of this study concluded that : 1) The basic learning model movement in long jump through a small game, students can learn effectively and efficiently. 2) Through learning approaches developed have shown the second grade students are more motivated and increase the amount of time students participate in the learning process follows the basic movement in long jump physical education subjects. The findings of this study have provided experience of elementary school students in physical activity motor foster interest, enthusiasm pleasant atmosphere of the physical education lessons.How to citeSumantri, M. (2015). Learning Model of Fundamental Long Jump Movement Based On Game Approach. Indonesian Journal Of Early Childhood Education Studies, 4(1), 35-41. doi:10.15294/ijeces.v4i1.9451